Analisis Faktor yang Mempengaruhi Terjadinya Gizi Berlebih Pada Bayi - Harahap, Anggita Putri; Sigalingging, Aldora Sri Oktovia; Fajarani , Annisa; Alfia , Assyari; Prasetio, Cilsilia Avindi; Nababan, Tiarnida (Journal of Pharmaceutical and Sciences, 2025)
Background: Overnutrition in infants aged 6-12 months is an increasingly prevalent health issue. The main factors suspected to play a role are maternal knowledge about nutrition and inappropriate feeding practices. Based on initial observations in Mekar Sari Village, Deli Serdang, 30 infants were found to be overnourished, indicating the need to identify the influencing factors. Objective: This study aimed to analyze the factors influencing the occurrence of overnutrition in infants aged 6-12 months, with a focus on maternal knowledge and feeding practices. Methods: The study used a cross-sectional design with a quantitative approach. Data were collected through interviews using questionnaires and anthropometric measurements. Infant nutritional status was determined based on Weight-for-Height (WHZ) measurements referring to WHO Growth Standards (2006), where infants were categorized as overnourished if the WHZ Z-score > +2 SD. The sample consisted of 30 infants who met the inclusion criteria. Results: WHZ measurements showed that 17 infants (56.7%) were overnourished. A total of 19 mothers (63.3%) had poor nutritional knowledge and 17 mothers (56.7%) implemented inappropriate feeding practices. Bivariate analysis showed significant relationships between overnutrition and maternal knowledge (p-value = 0.000; OR = 22.713) and feeding practices (p-value = 0.000). Conclusion: Maternal knowledge and feeding practices are factors that significantly influence the occurrence of overnutrition in infants at the research location. Public health interventions focusing on improving maternal nutritional literacy and promoting appropriate feeding practices are essential for preventing this problem.